2021
DOI: 10.3389/fphar.2020.614450
|View full text |Cite
|
Sign up to set email alerts
|

Cynandione A Alleviates Neuropathic Pain Through α7-nAChR-Dependent IL-10/β-Endorphin Signaling Complexes

Abstract: Cynandione A, an acetophenone isolated from Cynanchum Wilfordii Radix, exhibits antineuropathic pain effect. This study further explored the target molecule and signaling mechanisms underlying cynandione-A-induced antineuropathic pain. Intrathecal injection of cynandione A significantly attenuated mechanical allodynia in neuropathic rats and substantially increased spinal expression of IL-10 and β-endorphin but not dynorphin A. Cynandione A treatment also enhanced expression of IL-10 and β-endorphin but not α7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Accordingly, it has been demonstrated that increased IL-10 gene expression after exenatide administration is mediated by the cAMP/PKA/p38/CREB pathway [31]. Similar results were observed in mice, where the underlying mechanism of IL-10 release via α7-nAChR activation by cynandione also occurred through the cAMP/PKA/p38/CREB pathway [37]. IL-10 acts autocrinely when released by microglia, activating STAT3, which induces β-endorphin gene expression [31,36,37].…”
Section: Spinal Microglial Activation Increases Il-10/β-endorphin Levelsmentioning
confidence: 65%
See 2 more Smart Citations
“…Accordingly, it has been demonstrated that increased IL-10 gene expression after exenatide administration is mediated by the cAMP/PKA/p38/CREB pathway [31]. Similar results were observed in mice, where the underlying mechanism of IL-10 release via α7-nAChR activation by cynandione also occurred through the cAMP/PKA/p38/CREB pathway [37]. IL-10 acts autocrinely when released by microglia, activating STAT3, which induces β-endorphin gene expression [31,36,37].…”
Section: Spinal Microglial Activation Increases Il-10/β-endorphin Levelsmentioning
confidence: 65%
“…Recent evidence has demonstrated IL-10 and β-endorphin impact on pain control [30,[34][35][36][37][38][39][40][41][42][43]. Thus, studies analyzing these two protagonists were selected, in which microglia proved to be the main cell involved in this process, as shown in Table 1, Figure 2, and the graphical abstract.…”
Section: Pain Control By Il-10 Via β-Endorphin Release At the Spinal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, α7 nAChR agonists and allosteric modulators suppressed the release of proinflammatory cytokines in chronic pain models (Loram et al, 2010;Sun et al, 2017). More importantly, α7 nAChR agonists and allosteric modulators have shown potent analgesic effects (Bagdas et al, 2018b;Quadri et al, 2018;Wang et al, 2019;Arias et al, 2020;Han et al, 2020). Therefore, it is plausible that potentiation of the α7 nAChR may be a promising therapeutic strategy for the management of chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Cynandione A, a dimeric acetophenone that can be classified as abridged phenylpropanoid, or plant phenolics, is usually metabolized from tyrosine. It is an important bioactive marker of Cynanchum species, and was shown to possess neuroprotective [10,11], anti-inflammatory [11,12], hepatoprotective [13], and hypoglycemic [14] activities, as well as attenuating neuropathic pain [15].…”
Section: Introductionmentioning
confidence: 99%